The Grenada Revolution: Investigating the Ambitions and Shortcomings of a Radical Caribbean Political Experiment - Shenhat Haile (Caribbean Studies Students' Union, 2022)
In March 1979, the New Jewel Movement (NJM) transitioned into the People's Revolu- tionary Government (PRG) through a bloodless coup that for a time revolutionized the structure of governments in the Com- mon-law Caribbean. This policy review seeks to consider the success of the revolution based on: its aim of developing and sustaining a grassroots democracy, emphasis on mass education and its expansion of agribusiness initiatives as a part of broader industrialization efforts. Through an investigation of some of the critical events, ideological frameworks and ambitious political objectives that briefly transformed Grenadian society from 1979 to 1983 this review illustrates the complexity of the political experiment undertaken by the People's Revolutionary Government and argues that despite its short time span, the Grenada Revolution remains one of the most critical examples of revolutionary potential and radical self-rule in the twentieth-century Caribbean.